On stability of linear hybrid mechanical systems with distributed components - Martynyuk, A. A.; Slyn'ko, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We present a new approach to the solution of problems of stability of hybrid systems based on the constructive determination of elements of a matrix-valued functional.